Dialektika Agama dan Budaya dalam Sejarah Kesultanan Peureulak : Analisis Konflik Dinasti Aziziyah dan Dinasti Meurah - Miswari (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2024)
This article aims to analyze the existence of the Peureulak Kingdom which includes the background of its emergence, the integration of culture and religious values, and the conflict between the Aziziyah dynasty and the Meurah dynasty which was motivated by the Meurah dynasty's rejection of the Aziziyah dynasty's attitude which was considered too permissive towards cultural practices. which was considered by Meurah Muhammad Amin as the founder of the Meurah dynasty to contain elements of shirk. The research method used is a historical method with a qualitative approach. Researchers examine and critically analyze available sources in the form of writing, field evidence, and interviews with sources. The steps are topic selection, source collection, verification, interpretation, and writing. The research findings show that the presence of the heir to the Jeumpa Kingdom and the presence of the Caliph's Master greatly determined the emergence of the first Islamic kingdom in the archipelago, namely the Peureulak Sultanate. Then the first dynasty, namely the Aziziyah Dynasty, received opposition from Meurah Muhammad Amin because it was too permissive towards pre-Islamic culture. Resistance against the Aziziyah dynasty took place. The Aziziyah dynasty only lasted four periods and was then replaced by the Meurah dynasty. The Peureulak Sultanate was united hundreds of years later with the Pasai Sultanate.